2018
DOI: 10.1002/jbm.a.36454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphatidylserine‐containing supported lipid bilayers on the polarization of macrophages

Abstract: Placement of dental implants initiates inflammatory foreign body response, in which macrophages play a central role and affect the subsequent tissue healing process such as bone formation. The purpose of this study was to fabricate phosphatidylserine (PS)-containing supported lipid bilayers (SLBs) on a titanium surface to regulate the polarization of macrophages, a critical factor that affects following tissue healing and regeneration. The fluorescent recovery after photobleaching images showed that the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…40 Furthermore, other studies have confirmed that elongated macrophages on the surface of modified biomaterials exhibit the M2 phenotype. [41][42][43] However, some other studies have demonstrated opposing results. 44 Therefore, future research must investigate the detailed mechanisms through which TiO 2 nanotube surfaces regulate macrophage polarization.…”
mentioning
confidence: 99%
“…40 Furthermore, other studies have confirmed that elongated macrophages on the surface of modified biomaterials exhibit the M2 phenotype. [41][42][43] However, some other studies have demonstrated opposing results. 44 Therefore, future research must investigate the detailed mechanisms through which TiO 2 nanotube surfaces regulate macrophage polarization.…”
mentioning
confidence: 99%
“…When macrophages are activated into proinflammatory phenotype, that is M1, the cell morphology tends to be polygonal shaped with extended pseudopods. ,, As shown in Figure c, macrophages adhered to rPP transformed into irregular or polygonal shape with clear and long extended pseudopods, indicating the typical morphology of M1. , On PDA-PP, macrophages also spread but did not have the same long extended pseudopods as on rPP, which suggests decreased adhesion and moderate activation of macrophages. In contrast, macrophages adhered to coated meshes extended poorly and had a round-like shape.…”
Section: Resultsmentioning
confidence: 96%
“…A PS-containing supported phospholipid bilayer was bound to induce the M2 phenotype of RAW 264.7 cells on a Ti surface [20]. It was theorized that PS polarizes the macrophage-like cells by binding to the PS receptors, mimicking the interaction between apoptotic cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Ti surfaces coated with PS are also expected to induce M2 macrophage polarization and influence osseointegration. In fact, a supported lipid bilayer containing PS induced M2-like polarization of the murine macrophage cell line, RAW 264.7, on Ti surfaces [20]. Besides the formation of the lipid bilayer, Ti has been coated with PS-containing phospholipids through the evaporation of an organic solvent and the deposition of phospholipids on the Ti surface [18,21].…”
Section: Introductionmentioning
confidence: 99%